Muhafazakâr Sermayeye Sahip İşletmelerde Çalışan Uzman Meslek Sahibi Başörtülü Çalışanlar (Expert-Employees Wearing Headscarves Work in Businesses with Conservative Capital) - Meryem Karaca (İnsan & Toplum)
In this article, the impact on business life of the ongoing issue of the headscarf ban in the public sector will be examined, with particular attention to the relationship between employer and employee. More specifically, this article will focus on expert-employees and on conservative investorexpert-employees who wear headscarves This article isbased on written literature, research reports by a number of foundations and associations, writers, observations by sociologists and investors, and interviews with participants. made up of expert-employees who wear the headscarf and conservative investors.An “in-depth” method was used when conducting interviews in which there were twenty participants; eleven of which were expert-employees who wear headscarves, and nine were conservative investors. Three of the expert-employees were top level managers, while the other eight were middle level workers. During the interviews, a recording device was used for only one of the participants and notes were taken for the others. The duration of the interviews ranged from proximately two to two and a half hours without break. The history of the headscarf ban, its impact on people, how people’s notions and attitudes toward the headscarf have changed between the 1960s and 2000s, the direct and indirect effects of the headscarf ban in public places on the business life, and the perspectives held toward the headscarfby conservative-investors will be examined in this paper. As a result, it has been found that expert employees have been discriminated against in various areas and aspects of the professional world. Although their reasons may vary, examples can be seen in the job application process and in business life. The basic challenges expert-workers who wear headscarves face are restrictions in the amount of companies who will even consider hiring them, being assigned lower wages, and facing greater obstacles toward promotion.